(3TQM GdcaGjIs - (3GdORahdj, GdcGXej, YHO GdMSjf Hf eMeO Jbjs ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO, abO YQaJ aj Chd GdcJGH Cf GdeUfa (B... (3bO QJH cJGHg gfG Ydi eQGJH hebGUOs
(3BNQgG (B:s
(3hCeG GdGSJeQGQj aGdCbhi LhGRg dG hLhHg dYOe GdOdjd Ydi GdhLhH CUdG hEf bGd Hg HYV(B. (3gPG BNQ eG CQOfG HjGfg(B...s
(3JHUQI GdYfhGf (B:s
(3GdgOGjI aj TQM GdcaGjIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs